Effects of zinc supplementation on duration and action of botulinum toxin applied to face muscles: A systematic review of randomized clinical trials - Junior, Hélio Trindade; Melo, Caroline dos Santos; Mendes, Renata Rabello; Santos, Ramara Kadija Fonseca (Journal of Trace Elements and Minerals (Online), 2023)
•Supplementation of the 50 mg of zinc increased the duration of BT action in face muscles being dependent on the application objective.•It was not possible to determine the best type and dose of supplemental zinc to increase the duration of BT action in face muscles.•The insufficient number of RCTs did not permit agreement to the effect of zinc supplementation in the increase of the duration of BT action in face muscles. Zinc supplementation has been used to improve the effects of botulinum toxin (BT) on facial muscles. However, a scientific consensus regarding this has not been reached. We aimed to discuss the effects of zinc supplementation, isolated or phytase-associated, on the duration and action of BT in the face muscles of adults and the elderly. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines PRISMA and registered in the International Prospective Register of Systematic Reviews PROSPERO nº CRD420222319473, database searches were performed in PubMed, Embase, Lilacs, Bireme, Scope, Open Thesis, Cochrane Library, Clinical Trial, Web of Science, and Google Scholar using the Medical Subject Headings “botulinum toxin”, “zinc”, and “supplementation” in May 2023. Exclusion criteria: Studies involving children or teenagers. Inclusion criteria: Randomized clinical trials (RCTs), published as full-text versions developed with females and males at least 18 years old, that compared the effect of zinc supplementation on the duration and action of BT in facial muscles with a placebo. We are not delimited language and year of publication. All studies included as evaluated about risk of bias using the Revised Cochrane risk-of-bias tool for RCTs. Two RCTs were eligible, involving 123 individuals of both genders living in the United States of America and Egypt. In individual analysis of the studies the administration of mg.day−50 of zinc citrate supplemented with phytase increased the duration of BT treatment by 29.6% for the treatment of hemifacial spasms, blepharospasms, and cosmetic facial rhytids, according to the evaluators; 88% of the individuals treated for blepharospasms were “hard to treat” and 47% of those treated for blepharospasms were “easy to treat”, affirming improvements after BT intervention. Supplementation with mg.day−50 zinc gluconate without phytase increased the smiling-type commissure by 76.9%. The botulinum toxin is zinc-dependent metalloprotein but, was not scientific evidence to clinical practice of zinc supplementation for improve BT action in face muscle.